Endogenous polyamine content and metabolism in the ectomycorrhizal fungus Paxillus involutus - Fornalé, Silvia (The New phytologist, 1999)
Endogenous polyamine content of the ectomycorrhizal fungus Paxillus involutus, as well as the activity of its biosynthetic enzymes in relation to mycelia ageing were investigated in this work. Polyamines in free, PCA-soluble and insoluble conjugated forms, are present in Paxillus involutus mycelia in relatively high amounts and the ratio of putrescine to spermidine is age-dependent. Both arginine- and ornithine-decarboxylases are present, but putrescine biosynthesis proceeds mostly via ornithine decarboxylase and decreases with the age of mycelia. There was a large release of free polyamines from mycelia which showed age-dependent features. Clear polyamine uptake was observed in 2-wk-old mycelia and no competition between putrescine and cadaverine was detected. Putrescine uptake seems to reduce ornithine decarboxylase activity, but does not affect arginine decarboxylase